1)
-4x-8y=16
8x+16y=-16
Multiply fhe first equation by 2:
=> -8x - 16y = 32
Add this new equation with previous second equation
0 = 16, which means that the system has no solutions.
2)
4x-10y=-14
3x+8y=-26
Multiply the first equation by 3 and the second by - 4:
12x - 30y = - 42
-12x - 32y = 104
Add the two new equations
-------------------------
0 - 62y = 62
=> y = -1
replacing in the first equation:
=>
4x-10(-1) = -14
=> 4x + 10 = - 14
=> 4x = - 14 - 10
=> 4x = - 24
=> x = - 24 / 4
=> x = - 6
Answer: x = - 6 and y = - 1